Satisfaction Level Undergoing Patients Hemodialysis in Service Nursing in the Hemodialysis Unit Hemodialysis Efarina Hospital Etaham Berastagi - Pakpahan, Romauli (International Journal of Public Health Excellence (IJPHE), 2023)
Satisfaction patient is results achieved at the time privilege product service health respond need patient so that make you feel happy and comfortable . Study This aim For identify level satisfaction patients undergoing henodialysis in service nursing in the hemodialysis unit House Sick Efarina Etaham Berastagi. Study done on date July 2022 - August 2022 in the hemodialysis unit House Sick Efarina Etaham Berastagi with use consisting of a questionnaire of 2 parts namely demographic data and level satisfaction patients undergoing hemodialysis in service nursing. The Cronbach Alpha result is 0.85. The research design used is descriptive exploratory with big sample 50 people with method taking purposive sampling. Instruments used is compiled questionnaire with use scale linkert . Characteristics respondent and level satisfaction patient described use analysis descriptive for know frequency and percentage Where aspect satisfaction patient is described with serve average value each aspect. Research results show, characteristics respondent is male 70.0%, age "SI year 48.0%, religion Islamic 50.0%, Batak/Karo ethnicity 56.0%, junior high school education 40%, number Hemodialysis >432 times is 50.0%. satisfaction level patients undergoing hemodialysis in service nursing in a hospital hemodialysis unit Efarina Etaham Berastagi is 56% satisfied. Aspect highest from aspe satisfaction patient on service nursing is dimensions of tangibles deng the average value is 27.36. With thereby action nurse like recipient nurse moment enter room hd, explanation available facilities used, clean Pour, neatness uniform nurse Already Good according to respondents, and aspects ni must maintained and improved again. For increase maid: n nurse expected the Hospital.